The IL‐23/Th17 axis is involved in the adaptive immune response to Bacillus anthracis in humans. (2nd January 2014) - Harris, Kristina M.; Ramachandran, Girish; Basu, Subhendu; Rollins, Sandra; Mann, Dean; Cross, Alan S.
<x xml:space="preserve">Abstract</x> The neutralization of toxins is considered essential for protection against lethal infection with Bacillus anthracis (BA), a select agent and bioterrorism threat. However, toxin‐neutralizing activity alone would not be expected to provide sterile immunity. Therefore, we hypothesized that the development of an adaptive immune response against BA is required for bacterial clearance. We found that human monocyte‐derived dendritic cells (hDCs) kill germinated BA bacilli, but not nongerminated BA spores. hDCs produce IL‐1β, IL‐6, IL‐12, and IL‐23, and these cytokines are differentially regulated by germination‐proficient versus germination‐deficient BA spores. Moreover, the IL‐23 response to BA spores is regulated by IL‐1R‐mediated signaling. hDCs infected with germinating BA spores stimulated autologous CD4+ T cells to secrete IL‐17A and IFN‐γ in a contact‐dependent and antigen‐specific manner. The T‐cell response to BA spores was not recapitulated by hDCs infected with germination‐deficient BA spores, implying that the germination of spores into replicating bacilli triggers the proinflammatory cytokine response in hDCs. Our results provide primary evidence that hDCs can generate a BA‐specific Th17 response, and help elucidate the mechanisms involved. These novel findings suggest that the IL‐23/Th17 axis is involved in the immune response to anthrax in humans.